323 Health-Care Utilization and Bundled Payment Reimbursement for Patients Undergoing Anterior and Posterior Procedures for Degenerative Cervical Radiculopathy. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Alhourani, Ahmad; Sharma, Mayur; Ugiliweneza, Beatrice; Nuno, Miriam; Drazin, Doniel; Boakye, Maxwell
Abstract: INTRODUCTION: Anterior cervical discectomy with fusion (ACDF) or posterior cervical foraminotomy (PCF) are the surgical procedures performed to treat patients with degenerative cervical radiculopathy (DCR) METHODS: Data were extracted from MarketScan database (2000-2012), using ICD-9 and CPT-4 codes. Bundled payment was calculated as the cumulated payments from the index hospitalization admission to 90 d postsurgery discharge. We also analyzed the index hospitalization (physician, hospital as and total) and the postdischarge payments (hospital readmission, outpatient services, medications, and total). Groups were matched on the propensity score and number of levels operated on (single or multiple). RESULTS: A cohort of 3852 patients was identified from the database. A matched cohort of 2714 patients underwent multilevel surgery, while 1138 patients underwent single level surgery. Median 90-d bundle payment was significantly higher for ACDF compared to that for PCF for single-level (median 25 699 vs 15 263) and multilevel surgery (median 29 377 vs 16 295) P < .0001. The total index hospitalization payments (single level: median 22 870 vs 12 466, multilevel: median 26 730 vs 13 391), physician payment single level: median 4306 vs 1647, multilevel: median 5142 vs 2043), and hospital payments single level: median 12 438 vs 6764, multilevel: median 14 976 vs 7157), were higher for ACDF compared to PCF, P < .0001. There was no significant difference between the 2 procedures in overall 90-d postdischarge payments for both single and multilevel surgery (single level: median 1611 vs 1387, multilevel: median 1805 vs 1749, P -value >.25). CONCLUSION: Surgical treatment of DCR using ACDF generates higher health care resource utilization at the index hospitalization compared to PCF without any difference noted in 90-d postdischarge costs. PCF are an economically preferred option for bundled payment strategies.